Implementation of an automated dryer with solar collector (2022)
This research work consists of the development of an automated sustainable drying system using forced and preheated air to reduce the production time of handmade bricks, so a dryer witha solar collector wasimplemented to take advantage of the energy from solar radiation. A virtualinstrument was developed, which allows to visualize the variables of temperature and humidityinside the drying chamber, additionally a temperature control was implemented, this control allows the system to maintain a constant temperature during the drying process. Samples were taken from the production of the brick kiln “El Tejar” and dried by this device, thenthe drying times and their physical and mechanical properties were compared, finding that the bricks dried with the proposed prototype retained these properties. As for the compressive strength tests for samples of both processes was around 30.6 Kgf/cm² and 31.2 Kgf/cm², the deflection resistance was around 1.2 Kgf/cm² and 1.3 Kgf/cm², the initial absorption rate was around 0.3 g/cm²/min and 0.4 g/cm²/min, and finally the percentage of water absorption for both processes were around 12.9% and 13.1%. The difference lies in the drying times, since drying in the artisanal brick kilns takes about 15 daysin the proposed dryer takes 9 days, resulting in a decrease of 40% in this process.